A Legal Aesthetic of Medieval and Pre-Modern Arab-Muslim Urban Architectural Space - O’Meara, Simon (Journal of Arabic and Islamic Studies, 2017)
Despite growing scholarly awareness of an historical element of Islamic law concerning the regulation of the medieval and pre-modern Arab-Muslim medina’s architectural environment, a clear statement regarding the history, genealogy, nature, and reach of this element has yet to be made. The present article provides such a report and proposes that this element of Islamic law (fiqh al-bunyān) be considered a discourse that established a legal aesthetic of architectural space and contributed towards the replication of the medina environment.